Towards predicting the product quality in hot-melt extrusion: Pilot plant scale extrusion - Josip Matić; Carolina Alva; Simone Eder; Kathrin Reusch; Amrit Paudel; Johannes Khinast (Elsevier, 2021)
Following our study on the impact of hot melt extrusion (HME) process conditions on the product quality, we expanded our investigation to assessing the effect of scale-up on the product quality. To this end, we studied the influence of process settings and different scale-up variants on the active pharmaceutical ingredient (API) degradation in a pilot plant scale extruder. Six scale-up variants were investigated and none of them could replicate the product quality from the original process setup on a lab-scale extruder. By analyzing several process-dependent and -independent variables and cross referencing them to the experiments in the lab-scale extruder, we identified certain patterns. The results of the reduced order mechanistic 1D HME simulation of various process states made it possible to establish a correlation between the achieved API degradation and the local melt temperature and the exposure time in specific zones along the screw configuration. Since the same melt temperature and exposure time correlations were also valid for the lab scale-extruder, such an approach could be used in the future to predict the product quality as a function of processing conditions fully in silico prior to the first extrusion trials.